Motivating online language learning: exploring ideal L2 self, grit, and self-efficacy in relation to student satisfaction - Sun, Zhijie; Mu, Bingyu (Frontiers in Psychology, 2023)
Introduction This study delves into the intricate network of motivational factors that influence online learning satisfaction among intermediate-level English as a Foreign Language (EFL) students in mainland China. Methods A diverse sample of 496 EFL students participated in this research. Structural Equation Modeling was employed as the analytical method. Results The results of the study reveal significant and positive relationships between ideal L2 self and L2 grit with online learning satisfaction. Additionally, online learning self-efficacy emerged as a crucial mediator between ideal L2 self and online learning satisfaction, as well as between L2 grit and online learning satisfaction. Discussion These findings provide valuable insights into the motivational dynamics within online language learning contexts. They offer practical implications for educators and instructional designers seeking to enhance students’ online learning experiences.